Peran leader member exchange (LMX), kepribadian openness to experiences, dan harmonious passion dalam membentuk perilaku kerja yang inovatif - Brianita Riga Pratiwi; Endang Parahyanti (Jurnal Ilmiah Psikologi Terapan, 2022)
Innovative work behavior is considered an effective predictor of encouraging organizations to adapt to today's uncertain environment. This study aims to determine the harmonious role of the relationship between leader-member exchange and innovative work behavior through the mediation of personality openness to experience. Online survey used to employees from various fields of work in Indonesia. Through the snowball sampling technique, the researchers obtained a total sample of 327 people. The results of the study show that harmonious passion plays an indirect moderating role between leader-member exchange and IWB through openness to experience coefficientR2 of .37 in the model F(6, 320) = 31.27, P<.001. Moderated mediation index (model 14) harmonious relationship significantly moderated indirect relationship between LMX and IWB through openness to experience (b= .06, CI [.01,.11]). Thus, to bring up innovative work behavior in employees, the quality of relationships with superiors, personality, and passion have an important role.